Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have this:

j + k = (2a + 1) + (2b + 1)

j + k = 2a + 2b + 2

Is the extra 2 (in the second line) came from the sum of the two ones? What if I have this:

j + k = (3a + 3) + (4b + 3)

would be OK to simplify it like this

j + k = 3a + 4b + 6

Or there is a rule for that?

share|cite|improve this question
Yes, the $2$ comes from adding the two $1$s. Yes, it's correct to simplify to $3a+4b+6$. – Jeff Mar 12 '12 at 5:26
up vote 1 down vote accepted

Addition is associative and commutative:

$$\rm (a+b)+c=a+(b+c) \qquad\qquad a+b=b+a. $$

This ensures that parentheses, in the context of addition, are superfluous and can be invoked or discarded at will, and that summands can be permuted arbitrarily at will. Thus, e.g. $$\rm (2a+1)+(2b+1)=2a+1+2b+1=2a+2b+(1+1)=2a+2b+2.$$

share|cite|improve this answer

I think it would be fine like u wrote it. I guess the rule here is u can only sum up coefficients with same powers of the variables. so in your second case J + k = (3a^1 + 3a^0b^0) + (4b^1 + 3a^0b^0) = 3a = 4b + 6 like u said.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.